2017
DOI: 10.1080/01459740.2017.1329832
|View full text |Cite
|
Sign up to set email alerts
|

“My Whole Life is Ethics!” Ordinary Ethics and Gene Therapy Clinical Trials

Abstract: What and where is ethics in gene therapy? Historical debates have identified a set of ethical issues with the field, and current regulatory systems presume a discrete ethics that can be achieved or protected. Resisting attempts at demarcation or resolution, we use the notions of "ordinary" or "everyday" ethics to develop a better understanding of the complexities of experimental gene therapy for patients, families, and practitioners and create richer imaginings of ethics in the gene therapy sphere. Drawing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…While the boy received gene therapy treatment years ago, he continues to require half hour follow-up appointments for blood work and discussion of current and future medical care. This study demonstrates that patients may need to organize their life around their condition, including continuous medical monitoring, and that clinical care should shift to facilitate health and well-being of the patient post-gene therapy (Addison and Lassen 2017). In a mixed-methods study, all sickle cell disease stakeholders noted the potential burden of gene therapy trial involvement on participants.…”
Section: Results and Relevance To Germline Gene Editingmentioning
confidence: 95%
“…While the boy received gene therapy treatment years ago, he continues to require half hour follow-up appointments for blood work and discussion of current and future medical care. This study demonstrates that patients may need to organize their life around their condition, including continuous medical monitoring, and that clinical care should shift to facilitate health and well-being of the patient post-gene therapy (Addison and Lassen 2017). In a mixed-methods study, all sickle cell disease stakeholders noted the potential burden of gene therapy trial involvement on participants.…”
Section: Results and Relevance To Germline Gene Editingmentioning
confidence: 95%
“…This split of ‘ethics’ and ‘science’, which construes ‘ethics’ as a discrete, partible entity that can be neatly partitioned from ‘science’, has been met with sceptically by some medical experts (cf. Addison & Lassen 2017).…”
Section: The Research Ethics Apparatusmentioning
confidence: 99%
“…During my research, I came to understand this ‘origin story’ as a kind of recital that allowed practitioners to articulate their awareness of the field's darker but defining periods, and their current efforts to compensate for them. However, between this recounting of historic wrongs and the profound dominance of research ethics protocols in clinical settings, it was difficult to get people talking about their own ethical reasoning: ethics has become a brittle, bounded subject, synonymous with bureaucracy (Addison & Lassen 2017). I became interested in how this narrow ethical imagination shaped medical practice and patients’ experiences.…”
mentioning
confidence: 99%
“…Reddy (2007) discussed the bioethics of genetic engineering from community perspectives. Addison and Lassen (2017) study discussed genetic therapy and the balance between individual and community consent. As such, this paper posits that representations of anthropology, archaeozoology, and their relationship to the psychology of popular entertainment films in how they can engage students in exploring bioethics and related careers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an ethnographic study of a community's perceptions of genetic engineering in the United States, Reddy (2007) discussed some of the nuanced complexities of how bioethics intersected with the perceived utility of genetic engineering. Likewise, but from the perspective of medical practitioners, Addison and Lassen (2017) study suggested the nuanced perspectives toward genetic therapy.…”
Section: The Jurassic Park Series and Bioethics Implications In A Film Subgenrementioning
confidence: 99%